NUEVAS TENDENCIAS EN EL USO DE LA L1 - Martín Martín, José Miguel (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract This paper discusses certain changes that have taken place among theorists and publishers as regards the use of the mother tongue (L1) in EFL/ESL textbooks aimed at students who share a common L1. The general orthodoxy in the last three decades tended to consider that the L1 should not be present at all in either L2 classrooms or textbooks. This tendency seems to be shifting to a more comprehensive and flexible view of the role and possible use of the L1. Thus, nowadays a good number of textbooks with explicit use of L1 can be found in the Spanish market of EFL textbooks. This paper analyzes some of these textbooks, the activities they present in the L1 and the causes for the change.